The Synergistic Anti-Apoptosis Effects of Amniotic Epithelial Stem Cell Conditioned Medium and Ponesimod on the Oligodendrocyte Cells - Safaeinejad, Fahimeh; Asadi, Sareh; Ghafghazi, Shiva; Niknejad, Hassan (Frontiers in Pharmacology, 2021)
Multiple sclerosis is a chronic inflammatory and neurodegenerative disease of the CNS. The current treatment of MS is based on anti-inflammatory disease-modifying treatments, which can not regenerate myelin and eventually neurons. So, we need new approaches for axonal protection and remyelination. Amniotic epithelial stem cells (AECs), as a neuroprotective and neurogenic agent, are a proper source in tissue engineering and regenerative medicine. Due to differentiation capability and secretion of growth factors, AECs can be a candidate for the treatment of MS. Moreover, sphingosine‐1‐phosphate (S1P) receptor modulators were recently approved by FDA for MS. Ponesimod is an S1P receptor-1 modulator that acts selectively as an anti-inflammatory agent and provides a suitable microenvironment for the function of the other neuroprotective agents. In this study, due to the characteristics of AECs, they are considered a treatment option in MS. The conditioned medium of AECs concurrently with ponesimod was used to evaluate the viability of the oligodendrocyte cell line after induction of cell death by cuprizone. Cell viability after treatment by CM and ponesimod was increased compared to untreated groups. Also, the results showed that combination therapy with CM and ponesimod had a synergistic anti-apoptotic effect on oligodendrocyte cells. The combination treatment with CM and ponesimod reduced the expression of caspase-3, caspase-8, Bax, and Annexin V proteins and increased the relative Bcl-2/Bax ratio, indicating inhibition of apoptosis as a possible mechanism of action. Based on these promising results, combination therapy with amniotic stem cells and ponesimode could be a proper alternative for multiple sclerosis treatment.